Health Referral System for Non-Specialized Cases in Southeast Sulawesi Province, Indonesia - Risky, Sartini; Said, Faridah Moh; Said, Asbath; Hadju, Lodes (Al-Sihah: The Public Health Science Journal, 2021)
The government prioritizes health as one of the areas in which it seeks to boost the country’s growth, but the referral system in place has failed to deliver high-quality health care. The purpose of this study was to assess and empirically demonstrate the extent to which the health referral system has been implemented in Kendari Health Center and Bau-Bau City. The study was held in the Kendari City Health Center and the Bau-Bau City Health Center, and it lasted from February 2020 to February 2021. This research method is a qualitative approach based on postpositivism’s theory, in which the researcher is the primary instrument, triangulation is used to collect data, inductive data analysis is used to analyze data, and qualitative research results emphasize meaning rather than generalization. Informants in this study amounted to 15 informants. Qualitative data were analyzed using the NVIVO 12 QSR application. The research findings indicate that there is a conceptual link between the health system and the concept of implementing a referral system. This research emphasizes to the health service center the importance of increasing the knowledge of health workers through training for both doctors and advocacy for policymakers regarding the improvement of health facilities.